CHILD AND ADOLESCENT MENTAL HEALTH IN SCHOOLS: NURSES’ PERCEPTION - Bianchi, Bernardo Leivas; Siniak, Débora Schlotefeldt; Velozo, Kelly Dayane Stochero; Souza, Michele Bulhosa de; Borges, Luana Ribeiro (Cogitare Enfermagem, 2024)
Objective: To understand the perception of nurses who work in the School Health Program about mental health in children and adolescents. Method: This was a qualitative, exploratory, and descriptive study carried out between December 2022 and February 2023, with nurses working in Family Health Strategies in a municipality on the western border of Rio Grande do Sul - Brazil. Data collection with semi-structured interviews and Minayo’s Thematic Analysis. Results: The concept of mental health was linked to both the traditional concept and the expanded clinic. The risk factors for the mental health of children and adolescents highlighted were family conflicts, prejudice, exposure to violence, digital influence, the use of psychoactive substances, and crime. Conclusion: There is a need to promote care strategies, especially for nurses, enabling them to take a more critical look at risk factors and mental health demands based on the specific characteristics of children and adolescents.